Cultural Crossroads of the Korean Wave in Jambi City 2001-2020 - Fhirda Syiffa Almira; Nelly Indrayani; Hanif Risa Mustafa (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract : The purpose of writing this paper is to explain about the Korean wave   popular culture from South Korean. The beginning of the korean wave in Jambi was caused by the current of globalization. Advances in technology have made the korean wave spread rapidly. The phenomenon of the korean wave that has created fan groups in Jambi makes it interesting to research.The problems that will be of concern in conducting this research are what factors pushed the Korean wave   to enter Jambi, how was the development of the korean wave in Jambi and what was the impact of the Korean wave   on the people in Jambi. This study aims to find out how the history of the entry and development of Korean wave   popular culture has had an impact on the people of Jambi City. In this study using historical research methods. The techniques used for data collection are archives, literature studies, and interviews. The results of this study are that the Korean wave   entered Jambi City starting with the broadcast of Korean dramas on various television channels. The factor driving the entry and development of the korean wave was globalization resulting in advances in technology and information such as the internet and social media which created fan groups. The presence of the Korean wave   has an impact on society such as social, cultural and economic impacts. Abstrak : Penelitian ini membahas tentang budaya populer Korean wave . Di Kota Jambi, masuk dan berkembangnya korean wave ini di dukung dengan kemajuan di bidang teknologi dan komunikasi yang membuat persebaran dari produk korean wave semakin cepat. Hadir dan berkembangnya korean wave menciptakan kelompok penggemar. Fenomena ini menarik untuk diteliti. Adapun permasalahan yang akan menjadi perhatian dalam melakukan penelitian ini adalah bagaimana korean wave masuk dan berkembang ke Kota Jambi, dan bagaimana dampak Korean wave   terhadap masyarakat di Jambi. Penelitian ini bertujuan untuk mengetahui bagaimana sejarah masuk dan berkembangnya budaya populer korean wave hingga memberikan dampak terhadap masyarakat di Kota Jambi. Dalam penelitian ini menggunakan metode penelitian sejarah. Adapun teknik yang dilakukan untuk pengumpulan data yang digunakan adalah dengan menggunakan suber-sumber, studi pustaka, dan wawancara. Hasil penelitian ini adalah Korean wave   masuk di Kota Jambi diawali dengan tayangnya drama Korea di berbagai saluran televisi. Faktor yang mendorong masuk dan berkembangnya Korean wave adalah adanya globalisasi sehingga terjadi kemajuan di bidang teknologi dan informasi seperti internet dan media sosial yang menciptakan kelompok penggemar. Kehadiran korean wave  memberikan dampak sosial, budaya dan ekonomi.